The Use of Quizalize Media to Improve Arabic Listening Skills of Students at Nahdlatul Ulama University - Salsabila, Sarah; Rofiqi, Mohammad; Sriyono, Siti Amelia; Shodiq, Muhammad Jafar; Muliati, Ajeng Yuli (Mantiqu Tayr: Journal of Arabic Language, 2026)
The low listening ability of students in learning Arabic is caused by the use of learning media that is still conventional and less interactive. This study aims to examine the use of Quizalize as an interactive learning and evaluation medium in Arabic listening instruction and to explore students’ responses to its implementation. Employing a quantitative descriptive approach, the study involved third-semester students of the Interdisciplinary Islamic Studies Study Program at Nahdlatul Ulama University of Yogyakarta. Data were collected through a questionnaire designed to capture students’ perceptions of Quizalize in terms of usability, attractiveness, learning motivation, and perceived effectiveness. The results indicate that students responded positively to the use of Quizalize, particularly regarding increased engagement, ease of use, and immediate feedback during listening activities. These findings suggest that Quizalize supports a more interactive and student-centered learning environment and functions effectively as a formative evaluation tool in listening instruction. In conclusion, this study contributes to the growing body of research on digital learning media by highlighting the pedagogical value of Quizalize in Arabic language education. Future research is recommended to investigate its impact on other language skills and to employ experimental designs for measuring learning gains more comprehensively.